JURIDICAL ANALYSIS OF REGULATION NO. 15 OF 2020 CONCERNING THE TERMINATION OF PROSECUTION IN CRIMINAL OFFENSES IN THE PERSPECTIVE OF THE CRIMINAL JUSTICE SYSTEM IN INDONESIA - Aziz, Sultan Abdul; Sugilang, Sugilang; Prasetyo, Wahyu Wibowo; Asmara, Teddy; Harliyanto, Rois (Journal Of Social Science (JoSS), 2024)
The purpose of this study is to analyze: first, the study of Attorney General Regulation No. 15 of 2020 concerning the termination of prosecution based on restorative justice in the perspective of the criminal justice system in Indonesia. Second, the mechanism for terminating prosecution based on restorative justice based on Attorney General Regulation No. 15 of 2020 has fulfilled the requirements and objectives. This legal research uses a normative juridical approach method. The results of the study concluded that there is a contradiction between the position of Perja No. 15 of 2020 and the justice system in Indonesia. First, it shows that the findings in article 2 of Perja no 15 of 2020 "termination of prosecution based on restorative justice is carried out based on the principles of justice, public interest, proportionality, punishment as a last resort; and fast, simple, and low cost", Second, the mechanism for implementing restorative justice in embezzlement criminal cases consists of a) peace efforts. namely the peace process is carried out voluntarily, by deliberation for consensus, without pressure, coercion, and intimidation b) in the peace process, there are two possible mechanisms, namely rejection or success. The implementation of the peace agreement is divided into two ways, namely: 1) done by returning compensation 2) done by doing something.